Inequality and childhood overweight and obesity: a commentary. Issue 3 (17th March 2016) - Ulijaszek, S. J.; Pentecost, M.; Marcus, C.; Karpe, F.; Frühbeck, G.; Nowicka, P.
Summary: Statements on childhood overweight and obesity (COO) have focused on different avenues for prevention and treatment, critical stages of the life cycle, including pregnancy and lactation, individual, family, school and community‐based interventions, multidisciplinary family programmes and multicomponent interventions. This commentary is concerned with the less‐addressed relationship between COO and inequality. It describes current global patterns of inequality and COO and the ways in which those inequalities are linked to COO at micro‐level, meso‐level and macro‐level. It then describes current programmatic approaches for COO inequality, preventive and medical, and considers important pitfalls in the framing of the problem of COO and inequality. It ends with describing how childhood and adolescent overweight and obesity prevention and treatment programmes might be formulated within broader socio‐political frameworks to influence outcomes.